Immunological Oral Health Status of the Poultry Plants Employees - Kardashevska, O. I. (Journal of Education, Health and Sport, 2018)
Study of periodontal diseases gives us grounds for making a generalized conclusion that an appearance of abnormal changes in tissues holding teeth takes place on change of overall health and as a result of the influence of a set of internal and external factors, which define an approach to the treatment and prevention of these diseases. Despite automation and mechanization of poultry plants, much more poultry plants employees are influenced by adverse factors of production that leads to occupational diseases, partially to periodontal diseases. The aim of our work was to investigate a condition of the local nonspecific immunity among poultry plants employees having periodontal diseases. In research 50 poultry breeders having generalized periodontitis, who made a basic group, and 20 persons with generalized periodontitis forming a comparison group, who were not in contact with birds, took part. Findings were compared with data of 20 somatically healthy persons from the control group. In order to study a condition of the local resistance at generalized periodontitis under the influence of harmful factors of poultry production, certain immunity factors of capillary blood of gums and oral fluid were examined: IgM, IgG, IgA, SIgA, phagocytic index (PhI) and phagocytic number (PhN). The most significant changes in the local nonspecific protection factors were found among patients of the basic group: content of serum IgA was significantly below normal: 1,82±0,11 g/l. Increase in production of IgМ and IgG at decreasing content of IgA among persons from the basic group was indicative of functional tension of immunity humoral arm on antigen stimulation with streptococcal infection. A significant deficiency of SIgA in oral fluid (0,62±0,03 g/l) was detected that was two times less than values of the control group and by 1.3 less than in the comparison group. Phagocytosis percent, phagocytic number, and phagocytic index among the patients of the basic group were much higher if to be compared with the comparison and control groups. That was indicative of decrease in appropriate immune response among them. Thus, the findings have shown that permanent immunodysfunctions among the poultry plants employees having generalized periodontitis are increasing under the influence of the occupational pathogens related to poultry production.